Engineered drug delivery nanosystems for tumor microenvironment normalization therapy - Yang, Beining (2023)
As a complex “soil” ecosystem, the tumor microenvironment (TME) plays a crucial role in the occurrence, development and metastasis of tumors. Reprogramming TME can block the interactive network between tumors and extracellular matrix (ECM) / various surrounding cells and contribute to tumor effective damage, which is a potential therapeutic target in oncotherapy. Nanobiomaterials have received more attention due to their excellent drug loading and easy functionalization properties, which have been extensively integrated into the construction of engineered drug delivery nanosystems for TME normalization therapy. It has become a commanding point in the field of anti-tumor therapy. This review intends to present and analyze advanced nanotechnology strategies for normalizing TME from 7 different aspects including the reprogramming of extracellular matrix (ECM), cancer-associated fibroblasts (CAFs), abnormal blood vasculatures, hypoxia, tumor acidosis, tumor-associated macrophages (TAMs) and tumor immune tolerance microenvironment based on the various engineered drug delivery nanosystems. It also discusses the currently existing problems and future development trends, which are expected to be helpful for the translational application of nanomedicine in clinical cancer therapy.